1991
DOI: 10.1897/1552-8618(1991)10[185:mopath]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Pesticides and Their Hydrolysis Metabolites in Soil

Abstract: The soil thin layer chromatography technique was employed to assess the mobility of 21 chemicals (6 insecticides, 4 herbicides, and 11 of their hydrolysis metabolites) in 6 different soils The hydrolysis products of the four studied organophosphorus insecticides were significantly more mobile than their parent compounds, but the metabolites of carbamates, s triazines and phenoxy alkanoic acids were less mobile than their parent compounds For the chemicals for which signifi cant effects of soil variables were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…A large dipole moment implies a large degree of solvation. Therefore, the reactants are predicted to be more soluble in water than the hydrolysis products, in accord with experimental results; for example, the water solubility of atrazine is 70 mg litre −1 at 25 °C compared with 16 mg litre −1 for hydroxyatrazine 38…”
Section: Resultssupporting
confidence: 71%
“…A large dipole moment implies a large degree of solvation. Therefore, the reactants are predicted to be more soluble in water than the hydrolysis products, in accord with experimental results; for example, the water solubility of atrazine is 70 mg litre −1 at 25 °C compared with 16 mg litre −1 for hydroxyatrazine 38…”
Section: Resultssupporting
confidence: 71%
“…This may have a significant implication, especially when it is more mobile and more toxic to soil organisms than chlorpyrifos. Somasundaram et al (1991) reported that TCP is more mobile than chlorpyrifos using thin layer chromatography technique. It has been also reported that the toxicity of TCP (EC 50 = 18.6 mg/L) to Photobacterium phosphoreum, a soil bacterium, is 2.5-fold higher than its parent compound, chlorpyrifos (EC 50 = 46.3 mg/L) ).…”
Section: Tcp Degradationmentioning
confidence: 99%
“…It is therefore not surprising that trichlorophenol did not serve as a microbial substrate. The toxicity of trichlorophenol to microbes (Somasundaram et al, 1989b) and its low availability in soil (Somasundaram et al, 1989a) may contribute to the resistance of 2,4,5-T to the development of enhanced microbial degradation.…”
Section: Downloaded By [] At 15:29 03 February 2015mentioning
confidence: 99%
“…Racke and Coats (1987) believed that the formation of salicylic acid might be a key factor in the susceptibility of isofenphos to enhanced degradation. The low microbial toxicity (Somasundaram et al, 1989b), relative availability (reflected by its high mobility) (Somasundaram et al, 1989a), and its nutritive value may contribute to the potential for salicylic acid to condition soils for enhanced degradation of isofenphos.…”
Section: Downloaded By [] At 15:29 03 February 2015mentioning
confidence: 99%